Methodology for Wetland Seedbank Assays - Carrie Reinhardt Adams; Nancy M. Steigerwalt (EDIS)
ENH-1090, a 6-page illustrated fact sheet by Carrie Reinhardt Adams and Nancy M. Steigerwalt, summarizes standard techniques for wetland seed bank assays, including greenhouse set-up, sample collection and sample processing. Includes references. Published by the UF Department of Environmental Horticulture, February 2008.